Volume 3: Heat Transfer; Electric Power; Industrial and Cogeneration 2000
DOI: 10.1115/2000-gt-0201
|View full text |Cite
|
Sign up to set email alerts
|

High Freestream Turbulence Effects on Endwall Heat Transfer for a Gas Turbine Stator Vane

Abstract: High freestream turbulence along a gas turbine airfoil and strong secondary flows along the endwall have both been reported to significantly increase convective heat transfer. This study superimposes high freestream turbulence on the naturally occurring secondary flow vortices to determine the effects on the flowfield and the endwall convective heat transfer. Measured flowfield and heat transfer data were compared between low freestream turbulence levels (0.6%) and combustor simulated turbulence levels (19.5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…There are numerous end wall flow field and heat transfer studies. Radomski et al investigated the effect of high turbulence on end wall heat transfer. They found that the highest heat transfer is at the junction between the leading edge and the end wall.…”
Section: Fundamentals Of Heat Transfer In Gas Turbinesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous end wall flow field and heat transfer studies. Radomski et al investigated the effect of high turbulence on end wall heat transfer. They found that the highest heat transfer is at the junction between the leading edge and the end wall.…”
Section: Fundamentals Of Heat Transfer In Gas Turbinesmentioning
confidence: 99%
“…Radomski et al found that high free stream turbulence along a gas turbine aerofoil and strong secondary flows along the end wall significantly increased convective heat transfer. In this experiment, flow field and heat transfer data were measured and compared with low free stream turbulence levels of 0.6%.…”
Section: Modellingmentioning
confidence: 99%
“…Near the trailing edge, a significant increase in heat transfer exists mainly due to the strong mixing of two flows from both sides of the blade. The effect of free stream turbulence was considered in the study of Kang and Thole [10] and Radomsky and Thole [11]. It was found that the heat transfer increases as the turbulence intensity increases.…”
Section: Introductionmentioning
confidence: 99%